1984
DOI: 10.3382/ps.0630855
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Profiles of Broiler Stocks Fed Two Levels of Methionine and Lysine

Abstract: A phenotypic profile was compiled for eight commercial broiler stocks fed diets containing two levels of methionine and lysine. Stock by diet interactions were unimportant for most traits, although differences among stocks were somewhat magnified when they were fed the lower levels of methionine and lysine. Feed efficiency (body weight/feed consumption) to a fixed age was negatively associated with body weight, feed intake, frequency of leg disorders, and size of the abdominal fat pad. Its association with imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Regardless of diet, at all ages Line A males consumed more feed, grew faster, and utilized feed more efficiently than Line B males. Lack of line by diet interactions observed in the present experiment was consistent with previous reports (Siegel and Wisman,TABLE 8 1966; Marks et al, 1969;Siegel et al, 1984;Sorensen, 1985;Cahaner et al, 1987) and suggested that the most efficient broiler line should be used for evaluating all diets. Significant line by feeding regimen interactions have been reported for BW (Pinchasov et al, 1985;Nir et al, 1987).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Regardless of diet, at all ages Line A males consumed more feed, grew faster, and utilized feed more efficiently than Line B males. Lack of line by diet interactions observed in the present experiment was consistent with previous reports (Siegel and Wisman,TABLE 8 1966; Marks et al, 1969;Siegel et al, 1984;Sorensen, 1985;Cahaner et al, 1987) and suggested that the most efficient broiler line should be used for evaluating all diets. Significant line by feeding regimen interactions have been reported for BW (Pinchasov et al, 1985;Nir et al, 1987).…”
Section: Discussionsupporting
confidence: 95%
“…tors involved in this variation include growth rate, food intake, partitioning of energy for maintenance, synthesis of muscle protein and fat, ambient temperature, and subclinical infections (e.g., Siegel and Wisman, 1966;Peterson, 1970;Swain and Farrell, 1975;Walker and Farrell, 1976;Pym and Farrell, 1977;McCarthy and Siegel, 1983;Barbato et al, 1983;Siegel et al, 1984;Soller and Eitan, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral modifications in feed intake occurred concomitantly with selection for increased BW (Siegel et al, 1984). In the present experiment percentage carcass fat in the AL chickens was essentially double that of those fed on alternate days.…”
Section: Discussionmentioning
confidence: 60%
“…Negative correlations between antibody titers to SRBC and BW have been reported for chickens (Siegel et al, 1982(Siegel et al, , 1984van der Zijpp et al, 1987;Martin et al, 1988). Correlations between response to SRBC antigen and weights of bursa of Fabricius and thymus have been equivocal (Yamamoto and Glick, 1982;Ubosi et al, 1985;Martin et al, 1988).…”
Section: Introductionmentioning
confidence: 92%
“…It is well documented that derived AA requirements of growing chickens depend on many factors such as genotype, gender, age and investigated response parameters [ 18 , 19 , 20 , 21 , 22 ]. The applied modeling approach involves both the variation of daily protein deposition and predicted feed intake parameters.…”
Section: Resultsmentioning
confidence: 99%